A high temperature resistant dual phase cobalt-based high entropy alloy
By adding Al elements to the Cantor alloy system and using thermodynamic calculation to design a cobalt-based high-entropy alloy with a dual-phase structure, the problem of limited service temperature and easy precipitation of harmful phases in high-temperature environments is solved, and the high performance and high-temperature oxidation resistance of cobalt-based high-entropy alloys are achieved.
Patent Information
- Application Number
- CN202410934366.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Traditional high-temperature alloys have limited service temperature in high-temperature environments, making it difficult to reach more than 80% of the absolute temperature of their melting point, and are prone to precipitation of harmful phases at high temperatures, affecting performance.
Al element is added to the non-equal Cantor alloy system, and thermodynamic calculation is performed using CALPHAD technology and Thermo-Calc software to design a cobalt-based high-entropy alloy with FCC+HCP dual-phase structure. High-temperature resistant duplex cobalt-based high-entropy alloy is obtained through melt casting and heat treatment.
The high-throughput research and development of cobalt-based high-entropy alloys has been achieved, its performance has been improved, its performance has been shown to show excellent mechanical properties and high-temperature oxidation resistance, and is suitable for complex working conditions such as high temperature and high pressure.
Smart Images

Figure CN118880148B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a high-temperature resistant dual-phase cobalt-based high-entropy alloy. Background Art
[0002] High-performance metal materials play a key role in promoting the development of industrial civilization and scientific and technological progress. With the improvement of modern science and technology, the increasingly harsh working conditions such as high temperature, high pressure, and corrosion in the application fields of aerospace engines, gas turbines, automobile engines, energy industry, and precision manufacturing have put forward higher requirements on the service performance of metal materials.
[0003] At present, the main materials of industrial components in high-temperature environments are high-temperature alloys. Traditional high-temperature alloys include iron-based high-temperature alloys, nickel-based high-temperature alloys, cobalt-based high-temperature alloys, etc. However, this alloy based on the traditional design paradigm (a main element is combined with trace amounts of other elements to enhance the performance of the alloy) has encountered bottlenecks in further improving performance. On the one hand, the service temperature of traditional high-temperature alloys is limited by the melting point of its main element, and it is difficult to reach more than 80% of the absolute temperature of its melting point, and the improvement of temperature bearing capacity is extremely limited; on the other hand, the service temperature of the alloy is also affected by the stability of the alloy structure at high temperature. Traditional high-temperature alloys usually have a more complex phase structure, which increases the possibility of mutation of harmful phases at high temperatures. For example, the use temperature of iron-based high-temperature alloys can generally only reach 750-780℃, and harmful phases such as η, σ, μ, and Laves are easily precipitated when working under higher temperature conditions. Therefore, the research and development of alloy materials with better high-temperature performance is an urgent problem to be solved in the field of high-temperature engineering applications. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned prior art, the present invention proposes a high-temperature resistant dual-phase cobalt-based high-entropy alloy. By adding Al elements to the non-isotropic Cantor alloy system, and using the CALPHAD (CALculation of PHAse Diagram) technology, the thermodynamic calculation software Thermo-Calc is used to perform auxiliary design and simulation calculations of the multi-element system, and the phase composition of the alloy steady-state phase at a specific temperature and composition is predicted, and the alloy composition with a dual-phase structure is designed, and then the high-temperature resistant dual-phase cobalt-based high-entropy alloy is obtained through the steps of melting, casting, heat treatment, etc. The obtained high-temperature resistant dual-phase cobalt-based high-entropy alloy is a FCC+HCP dual-phase structure, which exhibits excellent mechanical properties and high-temperature oxidation resistance, and is suitable for a variety of complex working conditions such as high temperature and high pressure.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a high temperature resistant dual-phase cobalt-based high entropy alloy, which is obtained by adding Al element to a Co-Cr-Fe-Ni-Mn non-isotropic Cantor alloy system.
[0007] Preferably, the Al element accounts for 0-0.97% of the total mass of the high temperature resistant dual-phase cobalt-based high entropy alloy and is not 0%.
[0008] More preferably, the high temperature resistant dual-phase cobalt-based high entropy alloy comprises, by mass percentage, the following components:
[0009] Al: 0-0.97% and not 0%, Co: 48.17-49.72%, Cr: 27.70-28.02%, Fe: 7.44-7.53%, Ni: 7.82-7.91% and Mn: 7.32-7.40%.
[0010] Most preferably, the high temperature resistant dual-phase cobalt-based high entropy alloy comprises, by mass percentage, the following components:
[0011] Al: 0.24~0.48%, Co: 48.17~49.34%, Cr: 27.78~28.02%, Fe: 7.46~7.53%, Ni: 7.84~7.91% and Mn: 7.34~7.40%.
[0012] The second technical solution of the present invention is to provide a method for preparing the above-mentioned high temperature resistant dual-phase cobalt-based high entropy alloy, comprising the following steps:
[0013] The metal raw material is melted and then cast, the ingot is turned over and the melting is repeated 3 to 4 times, and after cooling, heat treatment is performed to obtain the high-temperature resistant dual-phase cobalt-based high-entropy alloy.
[0014] Preferably, the order of smelting the metal raw materials is from low to high melting points of the metal raw materials.
[0015] Preferably, the smelting is carried out in an argon atmosphere, with a heating rate of 10°C / min and a cooling rate of 5°C / min.
[0016] Preferably, after the repeated smelting of the tumbled ingot, a heat treatment at 1200° C. for 2 hours and then a water quenching step are further included, the purpose of which is to homogenize the alloy, eliminate the residual stress inside the alloy, and induce martensitic phase transformation.
[0017] The beneficial technical effects of the present invention are as follows:
[0018] The present invention utilizes CALPHAD technology and applies thermodynamic calculation software Thermo-Calc to perform auxiliary design and simulation calculation of multi-component systems, predicts the phase composition of the alloy steady-state phase at a specific temperature and composition, and designs an alloy composition with a dual-phase structure, thereby realizing high-throughput research and development of cobalt-based high-entropy alloys and improving the performance of the cobalt-based high-entropy alloys.
[0019] The high temperature resistant dual-phase cobalt-based high entropy alloy provided by the present invention is a FCC+HCP dual-phase structure, has the characteristics of a two-phase structure, a strength-ductility balance, and exhibits better mechanical properties. Its ultimate stress strength is 995-1525MPa, and its engineering strain is greater than 45%; the weight gain per unit area after oxidation at 600°C for 100h is less than 0.10mg / cm 2 After oxidizing at 800℃ for 100h, the weight gain per unit area is less than 0.21mg / cm 2 After 1000℃ oxidation for 100h, the weight gain per unit area is less than 1.52mg / cm 2 Compared with the typical nickel-based alloy TMS238 under the same oxidation conditions, its high-temperature oxidation resistance is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 ECCI diagrams of typical structures of cobalt-based high entropy alloys prepared in Examples 1-5, wherein A is the ECCI diagram of the typical structure of a cobalt-based high entropy alloy of CA0, B is the ECCI diagram of the typical structure of a cobalt-based high entropy alloy of CA1, C is the ECCI diagram of the typical structure of a cobalt-based high entropy alloy of CA2, D is the ECCI diagram of the typical structure of a cobalt-based high entropy alloy of CA3, and E is the ECCI diagram of the typical structure of a cobalt-based high entropy alloy of CA4.
[0021] Figure 2 Engineering stress-strain curves of the cobalt-based high entropy alloys prepared in Examples 1-5.
[0022] Figure 3 Oxidation kinetic curves of the cobalt-based high entropy alloys prepared in Examples 1-5 and the nickel-based alloy TMS238 of Comparative Example 1 oxidized at 600°C for 100 hours.
[0023] Figure 4 Oxidation kinetic curves of the cobalt-based high entropy alloys prepared in Examples 1-5 and the nickel-based alloy TMS238 of Comparative Example 1 oxidized at 800°C for 100 hours.
[0024] Figure 5 Oxidation kinetic curves of the cobalt-based high entropy alloys prepared in Examples 1-5 and the nickel-based alloy TMS238 of Comparative Example 1 oxidized at 1000°C for 100 hours. DETAILED DESCRIPTION
[0025] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0026] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0027] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] Example 1
[0030] The cobalt-based high entropy alloy of this embodiment contains five elements: Co, Cr, Fe, Ni, and Mn, and the mass percentage of each element is: Co: 49.72%, Cr: 27.70%, Fe: 7.44%, Ni: 7.82%, Mn: 7.32%, denoted as CA0.
[0031] The preparation process of the cobalt-based high entropy alloy of this embodiment is as follows: 1) according to the designed composition, pure metal particles with a purity of 99.95wt.% are selected to prepare sufficient raw materials, the oxide film on the surface of the metal particles is removed with a steel brush, the single-substance particles are ultrasonically cleaned in anhydrous ethanol for 2 minutes to remove oil and impurities on the metal surface, and the particles are taken out and blown dry with cold air for use; 2) Co: 49.72g, Cr: 27.70g, Fe: 7.44g, Ni: 7.82g, Mn: 7.32g are weighed with an electronic balance with an accuracy of 0.0001g; 3) the raw materials are placed in the working chamber of the vacuum induction furnace in the order of melting point from low to high, and the vacuum is evacuated to 6.7×10 -3 Pa, then high-purity argon gas with a purity of 99.99wt.% was introduced, the current was 700A, the heating rate of the melting furnace was 10℃ / min, and the cooling rate was 5℃ / min; 4) the furnace was taken out and cast in 5) turning the ingot over and repeating the smelting for 3 times; 6) after natural cooling, performing a constant temperature heat treatment at 1200°C for 2h, and then rapidly cooling to room temperature by water quenching to obtain a cobalt-based high entropy alloy ingot.
[0032] Example 2
[0033] The only difference from Example 1 is that its cobalt-based high entropy alloy consists of the following chemical components in mass percentage: Al: 0.24%, Co: 49.34%, Cr: 27.78%, Fe: 7.46%, Ni: 7.84%, Mn: 7.34%, denoted as CA1.
[0034] Example 3
[0035] The only difference from Example 1 is that its cobalt-based high entropy alloy consists of the following chemical components in mass percentage: Al: 0.48%, Co: 48.95%, Cr: 27.87%, Fe: 7.48%, Ni: 7.86%, Mn: 7.36%, denoted as CA2.
[0036] Example 4
[0037] The only difference from Example 1 is that its cobalt-based high entropy alloy consists of the following chemical components in mass percentage: Al: 0.73%, Co: 48.56%, Cr: 27.94%, Fe: 7.50%, Ni: 7.89%, Mn: 7.38%, denoted as CA3.
[0038] Example 5
[0039] The only difference from Example 1 is that its cobalt-based high entropy alloy consists of the following chemical components in mass percentage: Al: 0.97%, Co: 48.17%, Cr: 28.02%, Fe: 7.53%, Ni: 7.91%, Mn: 7.40%, denoted as CA4.
[0040] Comparative Example 1
[0041] This comparative example is a nickel-based single crystal high-temperature alloy TMS238, which contains ten elements: Ni, Ta, Co, Re, Al, Ru, Cr, W, Mo, and Hf. The mass percentage of each element is: Ni: 58.66%, Ta: 7.70%, Co: 6.51%, Re: 6.46%, Al: 5.91%, Ru: 4.94%, Cr: 4.59%, W: 4.06%, Mo: 1.06%, Hf: 0.11%, denoted as R1.
[0042] The preparation process of the comparative alloy is as follows: 1) according to the alloy composition, pure metal particles with a purity of 99.95wt.% are selected to prepare sufficient raw materials, the oxide film on the surface of the metal particles is removed with a steel brush, the single-substance particles are ultrasonically cleaned in anhydrous ethanol for 2 minutes to remove oil and impurities on the metal surface, and the particles are taken out and blown dry with cold air for later use; 2) Ni: 58.66g, Ta: 7.70g, Co: 6.51g, Re: 6.46g, Al: 5.91g, Ru: 4.94g, Cr: 4.59g, W: 4.06g, Mo: 1.06g, Hf: 0.11g are weighed with an electronic balance with an accuracy of 0.0001g; 3) the raw materials are placed in the working chamber of a vacuum induction furnace in the order of melting point from low to high, and the vacuum is evacuated to 6.7×10 -3 Pa, then high-purity argon gas with a purity of 99.99wt.% was introduced, the current was 1000A, the heating rate of the melting furnace was 10℃ / min, and the cooling rate was 5℃ / min; 4) the furnace was taken out and cast in 5) turning the ingot over and repeating the smelting for 4 times; 6) after natural cooling, performing a constant temperature heat treatment at 1200°C for 2h, and then rapidly cooling to room temperature by water quenching to obtain a TMS238 alloy ingot.
[0043] The ECCI diagram of the typical structure of the cobalt-based high entropy alloy prepared in Example 1-5 is shown in Figure 1 , where A is the ECCI diagram of the typical organization of the cobalt-based high entropy alloy of CA0, B is the ECCI diagram of the typical organization of the cobalt-based high entropy alloy of CA1, C is the ECCI diagram of the typical organization of the cobalt-based high entropy alloy of CA2, D is the ECCI diagram of the typical organization of the cobalt-based high entropy alloy of CA3, and E is the ECCI diagram of the typical organization of the cobalt-based high entropy alloy of CA4. Figure 1 It can be seen that after homogenization, the five cobalt-based high-entropy alloys all showed obvious alternating distribution of light and dark stripes, representing different crystal plane orientations, proving the existence of FCC phase and lath-shaped HCP martensite phase in the alloy, and the alloy has a FCC+HCP dual-phase structure.
[0044] The mechanical properties of the cobalt-based high entropy alloys prepared in Examples 1-5 were tested, and the specific testing steps were as follows:
[0045] 1) The heat-treated cobalt-based high-entropy alloy ingot is cut into alloy samples with a specification of 5 mm × 5 mm × 10 mm by a wire cutting machine, and the surface is polished to 600 mesh;
[0046] 2) A microcomputer-controlled electronic universal testing machine was used to carry out compression tests on the alloy samples at room temperature, with a compression rate of 0.002 mm / s.
[0047] Test results such as Figure 2 As shown, the ultimate stress strength and engineering strain rate of each embodiment are shown in Table 1.
[0048] Table 1 Ultimate stress strength and engineering strain rate of alloys
[0049] Alloy Name Ultimate stress strength (MPa) Engineering strain (%) CA0 1180 46.4 CA1 1324 59.7 CA2 1525 64.0 CA3 957 57.6 CA4 995 52.8
[0050] Figure 2 The results in Table 1 indicate that the phase transformation induced plasticity of the FCC+HCP dual-phase high entropy alloy prepared in the present invention realizes the TRIP effect, which can coordinate the balance between high strength and high ductility of the material, and enable the material to have excellent mechanical properties.
[0051] According to HB5258-2000 "Test Method for Oxidation Resistance Evaluation of Steel and High-temperature Alloys", a high-temperature oxidation test plan was formulated to compare the high-temperature oxidation conditions of the alloys prepared in Examples 1-5 and Comparative Example 1. The specific test steps are as follows:
[0052] 1) A square sample with a size of 5 mm×5 mm×4.5 mm was cut from the alloy ingots prepared in each embodiment and comparative example. To ensure the reliability of the experimental data, three sets of parallel experiments were set for the alloy samples in each embodiment and comparative example;
[0053] 2) All six surfaces of the alloy specimen were sanded to 3000 mesh to ensure that there was no oxide coverage on the surface of the specimen before the experiment;
[0054] 2) After cleaning and drying, use an electronic analytical balance with an error of 0.0001g to measure the initial weight of the alloy and record it;
[0055] 3) The corundum crucible is used as a sample container in the oxidation experiment. It needs to be dried at 110°C for 2 hours in advance to remove residual moisture and store dry;
[0056] 4) The three groups of parallel samples of each embodiment and comparative example that have been pretreated are placed in a corundum crucible at intervals and sent into the middle section of a tube furnace at a heating rate of 4° C. / min;
[0057] 5) The samples were subjected to constant temperature oxidation experiments in air atmosphere at 600°C, 800°C and 1000°C respectively, and the weight of the samples after oxidation was measured and recorded every 10 hours;
[0058] 6) The test was terminated after 100 hours, and the oxidation weight gain of different alloys after 100 hours of constant temperature oxidation treatment was calculated, and the oxidation kinetics curve was drawn.
[0059] The test results at 600°C are shown in Figure 3 , Figure 3 It shows that the weight gain per unit area of Examples 1-5 and Comparative Example 1 after oxidation at 600°C for 100h is 0.073 mg / cm 2 , 0.026mg / cm 2 , 0.033mg / cm 2, 0.065mg / cm 2 , 0.096mg / cm 2 、0.160mg / cm 2 At this temperature, the weight gain of the alloy was not obvious. There was no obvious difference in weight gain between Examples 1-5. There was a slight mass change in the first 20 hours of oxidation (initial oxidation stage). However, after the oxide film was formed, the weight gain rate decreased rapidly and the weight gain curve became flat. The oxidation rate constant (K p ) can be obtained by the formula (Δm / A) 2 =K p t calculation. Where Δm is the weight gain of the sample due to oxidation, in mg; A is the surface area of the sample, in cm 2 ; K p is the oxidation rate constant; t is the oxidation time, in h. The oxidation rate constants (K p ) are 5.329×10 -5 mg 2 / cm 4 h, 0.676×10 -5 mg 2 / cm 4 h, 1.063×10 -5 mg 2 / cm 4 h, 4.238×10 -5 mg 2 / cm 4 h、9.120×10 -5 mg 2 / cm 4 h, 25.568×10 -5 mg 2 / cm 4 h. This indicates that both the alloy system of the present invention and the reference sample have excellent anti-oxidation properties in a relatively low temperature environment.
[0060] The test results at 800°C are shown in Figure 4 , Figure 4 It shows that the oxidation weight gain per unit area of Examples 1-5 and Comparative Example 1 after oxidation at 800°C for 100h is 0.203 mg / cm 2 、0.179mg / cm 2 、0.173mg / cm 2 , 0.199mg / cm 2 , 0.202mg / cm 2 , 2.985mg / cm 2 ; The oxidation rate constants are 4.121×10 -4 mg 2 / cm 4 h, 3.201×10 -4 mg 2 / cm 4 h, 2.986×10 -4 mg 2 / cm 4 h, 3.960×10 -4 mg 2 / cm 4 h, 4.064×10 -4 mg 2 / cm 4 h、890.903×10 -4 mg 2 / cm 4 h. The oxidation weight gain of Examples 1-5 is still not obvious. The first 10h of the oxidation process is in the rapid oxidation stage. An oxide film quickly forms on the alloy surface, which effectively prevents oxygen atoms from penetrating into the alloy and reduces the oxidation rate. As the oxidation time increases, the weight gain trend slows down, and the weight gain rate is significantly lower than that of the previous stage. The oxidation curve tends to be flat in the later stage, and the alloy sample reaches steady-state oxidation and enters the oxidation passivation period. Examples 1-5 still have excellent antioxidant properties at this temperature; Comparative Example 1 has a large oxidation weight gain and a significant decrease in antioxidant properties.
[0061] Test results at 1000°C are shown in Figure 5 , Figure 5 It shows that the oxidation weight gain per unit area of Examples 1-5 and Comparative Example 1 after oxidation at 1000°C for 100h is 0.892 mg / cm 2 , 0.776mg / cm 2 、0.823mg / cm 2 、1.135mg / cm 2 、1.519mg / cm 2 , 9.069mg / cm 2 ; The oxidation rate constants are 7.957×10 -3 mg 2 / cm 4 h, 6.026×10 -3 mg 2 / cm 4 h, 6.767×10 -3 mg 2 / cm 4 h, 12.875×10 -3 mg 2 / cm 4 h、23.080×10 -3 mg 2 / cm 4h、822.540×10 - 3 mg 2 / cm 4 h. The oxidation rate of Examples 1-5 gradually decreases, and the oxidation weight gain curve tends to be stable at 90-100h, and the anti-oxidation performance is good. Comparative Example 1 loses weight in the late oxidation period because the surface oxide of the alloy peels off from the matrix in the late oxidation period, loses its protective effect, and the alloy matrix is exposed and continues to oxidize, but the oxidation weight gain is much less than the oxide shedding amount, and the alloy has poor anti-oxidation performance at this temperature.
[0062] Through the above performance verification test, it can be seen that the two with the best high-temperature oxidation resistance and compression mechanical properties among the five cobalt-based high-entropy alloys provided in Examples 1-5 are CA1 and CA2. In addition, during the research process, CA1 also showed the best room-temperature corrosion resistance. The present invention has important application and research value in the field of high-temperature engineering materials such as automobile gas turbines and aerospace engines.
[0063] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A high temperature resistant dual phase cobalt-based high entropy alloy, characterized in that: The high temperature resistant dual-phase cobalt-based high entropy alloy comprises the following components in terms of mass percentage: Al: 0.24~0.48%, Co: 48.17~49.34%, Cr: 27.78~28.02%, Fe: 7.46~7.53%, Ni: 7.84~7.91% and Mn: 7.34~7.40%; The ultimate stress strength of the high-temperature resistant dual-phase cobalt-based high-entropy alloy is 1324-1525 MPa, the engineering strain is greater than 59.7%, and the weight gain per unit area after oxidation at 600 ° C for 100 h is less than 0.033 mg / cm 2 After oxidation at 800 °C for 100 h, the oxidation weight gain per unit area is less than 0.179 mg / cm 2 After oxidation at 1000 °C for 100 h, the weight gain per unit area was less than 0.823 mg / cm 2 .
2. A method for preparing the high temperature resistant dual-phase cobalt-based high entropy alloy according to claim 1, characterized in that: The following steps are involved: The metal raw material is melted and then cast, the ingot is turned over and the melting is repeated 3 to 4 times, and after cooling, heat treatment is performed to obtain the high-temperature resistant dual-phase cobalt-based high-entropy alloy.
3. The preparation method according to claim 2, characterized in that: The order of smelting the metal raw materials is from low to high melting points.
4. The preparation method according to claim 2, characterized in that: The smelting is carried out in an argon atmosphere, with a heating rate of 10°C / min and a cooling rate of 5°C / min.
5. The preparation method according to claim 2, characterized in that: After the ingot is repeatedly smelted, the method further includes a step of heat treatment at 1200° C. for 2 h and then water quenching.
Citation Information
Patent Citations
High entropy alloy having TWIP / trip property and manufacturing method for the same
KR101748836B1
Stress-induced phase transformable dual-phase high entropy alloy and manufacturing method for the same
KR1020180041407A